2012
DOI: 10.1145/2408736.2408742
|View full text |Cite
|
Sign up to set email alerts
|

Data mining methodologies for pharmacovigilance

Abstract: Medicines are designed to cure, treat, or prevent diseases; however, there are also risks in taking any medicine -particularly short term or long term adverse drug reactions (ADRs) can cause serious harm to patients. Adverse drug events have been estimated to cause over 700,000 emergency department visits each year in the United States. Thus, for medication safety, ADR monitoring is required for each drug throughout its life cycle, including early stages of drug design, different phases of clinical trials, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 64 publications
(60 reference statements)
0
10
0
2
Order By: Relevance
“…The advent of electronic medical records (EMR) in healthcare systems provides opportunity to harness the power of data mining via rule‐based or machine learning algorithms to detect and build catalogues for DILI. Several studies have looked into detection of adverse drug events (ADE) using routinely collected data such as diagnosis codes and laboratory parameters . Nonetheless, this is particularly challenging for DILI because competing aetiologies mimicking DILI have to be ruled out via a diagnostic algorithm that incorporates careful physical examination, history taking and a series of serological and imaging tests .…”
Section: Introductionmentioning
confidence: 99%
“…The advent of electronic medical records (EMR) in healthcare systems provides opportunity to harness the power of data mining via rule‐based or machine learning algorithms to detect and build catalogues for DILI. Several studies have looked into detection of adverse drug events (ADE) using routinely collected data such as diagnosis codes and laboratory parameters . Nonetheless, this is particularly challenging for DILI because competing aetiologies mimicking DILI have to be ruled out via a diagnostic algorithm that incorporates careful physical examination, history taking and a series of serological and imaging tests .…”
Section: Introductionmentioning
confidence: 99%
“…These in silico findings were supported by in vitro receptor‐ and transporter‐binding studies 40 . The key concepts and recent advances of these approaches have been reviewed elsewhere 9 , 38 , 41 , 42 , 43 , 44 , 45 …”
Section: Operationalizing a Systems Approach: Examplesmentioning
confidence: 81%
“…However, when taking any medication, some risks should be taken seriously. Severe adverse drug reactions (ADRs) can lead to patient morbidity [1]. In the U.S., ADRs have been Moreover, some studies have indicated that many Taiwanese, who are Han Chinese, have a gene called HLA-B 1502, which increases the risk of SJS induced by medications [35,36].…”
Section: Introductionmentioning
confidence: 99%